2008
DOI: 10.1057/pm.2008.12
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age and income on retirement decisions: A comparative analysis between Italy and the UK

Abstract: has a PhD in Pensions, she is the Head of the Finance and Business Law Department at the Westminster Business School and the Director of the Pension Investment Academy. Orla has published numerous articles and has wide experience of pension matters. Roberta Adamiis a senior lecturer in Finance at the University of Westminster and a visiting lecturer at the University of Bologna. She was formerly a Financial Analyst at Citibank and Tokai Bank, Europe. Roberta has spoken at numerous conferences and contributed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As Gough et al (2008) have noted by investigating the relationship between income and retirement age, they concluded that high earners retire relatively early, while those in the lowest income groups tend to retire later. This may, however, be the situation in exception of ill-health, industrial accidents, or accidents of any form.…”
Section: Figure 3 Long-term Planning Measuresmentioning
confidence: 88%
See 3 more Smart Citations
“…As Gough et al (2008) have noted by investigating the relationship between income and retirement age, they concluded that high earners retire relatively early, while those in the lowest income groups tend to retire later. This may, however, be the situation in exception of ill-health, industrial accidents, or accidents of any form.…”
Section: Figure 3 Long-term Planning Measuresmentioning
confidence: 88%
“…To the contrary, shortening the time of employment and a more extended period of retirement would lead to very low pensions, higher tax burdens on workers, and slower economic growth. Age reduction is also reflective and/or harbors sentiments of age discrimination at the workplace and the public space (Gough, Adami and Waters, 2008;Quadagno, 2014), which is pushing people to maintain a youthful appearance (Quadagno, 2014), utilizing anti-ageing products. Thus, connoting an adaptation mechanism for perpetrators.…”
Section: The Dynamics Of Age Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Gough et al (2008), in a study on the relationship between pension reforms, retirement age, pay and decision had concluded that in both countries Italy and the UK, high income earners retired relatively early. On the same note, the lowest income earners group tend to retire later.…”
Section: Literature Reviewmentioning
confidence: 99%